Comprehensive stress management - Greenberg, Jerrold S. (New York : McGraw-Hill Higher Education, 2011)
"Comprehensive Stress Management helps students identify, understand, and manage the stressors that most affect their lives. Written in an informal, anecdotal style, the text presents the latest research findings on the physical, psychological, sociological, and spiritual aspects of stress. The text also provides an in-depth discussion of a wide variety of coping skills, including relaxation techniques, behavior change interventions, and strategies for defusing physiological arousal. This engaging, easy-to-read text gives students the tools they need to cope with stress in an increasingly stressful world. Accompanying the text are instructor and student resources on the Online Learning Center"--Provided by publisher.
Machine generated contents note: Part 1 : Scientific Foundations 1: What is Stress? 2: Stress Psychophysiology 3: Stress and Illness/Disease Part 2: General Applications: Life Situation and Perception Interventions 4: Intervention 5: Life-Situation Interventions: Intrapersonal 6: Life-Situation Interventions: Interpersonal 7: Perception Interventions 8: Spirituality and Stress Part 3: General Applications: Relaxation Techniques 9: Meditation 10: Autogenic Training, Progressive Relaxation and, Imagery 11: Other Relaxation Techniques Part 4:General Applications: Physiological Arousal and Behavior Change Interventions 12: Physiological Arousal Interventions13: Strategies for Decreasing Stressful Behaviors 14: Diversity and Stress Part 5: Specific Applications 15: Occupational Stress 16: Stress and the College Student 17: Family Stress 18: Stress and Older Adults.
Includes bibliographical references and index.
Keywords: Stress (Psychology); Stress (Physiology); Stress (Psychology) -- Prevention; Stress management